Telomere length shortening is associated with disease evolution in chronic myelogenous leukemia. - Boultwood, J; Fidler, C; Shepherd, P; Watkins, F; Snowball, J; Haynes, S; Kusec, R; Gaiger, A; Littlewood, T; Peniket, A; Wainscoat, J (1999)
We studied telomere length in the peripheral blood leukocyte samples of a large group of patients with chronic myelogenous leukemia (CML) by Southern blot hybridization using the (TTAGGG)4 probe. The average telomere length expressed as the peak telomere repeat array (TRA) of the peripheral blood samples obtained from a group of 34 healthy age-matched controls ranged between 7.6 and 10.0 kb and the mean peak TRA was 8.7 kb. Forty-one patients in the chronic phase of CML were studied; 32/41 (78%) showed telomere reduction (<7.6 kb) relative to age-matched controls and the mean peak TRA was 6.4 kb (range 4.0-10.6 kb). Serial samples were analysed from 12 patients at both chronic phase and during disease progression. The leukocyte DNA of all 12 patients in accelerated phase and/or blast crisis showed telomere reduction relative to age-matched controls and the mean peak TRA was 4.1 kb (range 3.0-5.4 kb). The peak TRA in the accelerated or blast phase was reduced compared with the corresponding paired sample in the chronic phase in all cases studied. These data show that a marked reduction in telomere length is associated with disease progression in CML.